IMPACT OF SURFACE IRRIGATION MANAGEMENT ON WHEAT YIELD AND QUALITY PARAMETERS IN EGYPT - Tarek Mahmoud ATTAFY; Mohamed Sobhy KHATAB; Nermeen Mohammed TOLBA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This research was conducted at El-Gemmeiza Agricultural Research Station, Gharbia Governorate, middle of the Nile Delta, Egypt, during the winter seasons of 2021/2022 and 2022/2023 to determine the effect of different bed-furrow irrigation management strategies on irrigation efficiency, wheat grain yield and its components and quality parameters. The field experiment was designed in RCBD and included: basin-flooding (control, Tf) and bed-furrow with three irrigation times as a percentage of advance time (Ta); T1=Ta,T2=1.20Ta, and T3=1.30Ta. The results revealed that; increasing irrigation time had a simple effect on the Ta while had an obvious effect on the depletion and recession time. The T1 saved 23.3% of irrigation water compared to the Tf, increasing irrigation time increased water applied. The soil moisture content in the Tf was higher than in the bed-furrow treatments. Increasing irrigation time increased the moisture content in the furrows and within the beds. Bed-furrow enhanced irrigation efficiency compared to Tf. The highest application efficiency and distribution uniformity values were 76.6, 74.7 and 80.7, 82.3%, which were achieved by T3 treatment. Bed-furrow increased wheat grain yield compared to Tf. The T3 treatment is superior in grain yield with values of 3107 and 3185 kg fed-1.Bed-furrow enhanced the 1000 grain weight and spike length, while Tf surpassed in the number of spikes and straw yield. The highest water productivity was 1.87 and 1.67 kg m-3 achieved by T1. There is no significant difference in quality parameters except for dry gluten, the highest values achieved by T2 treatment.